Reynolds-Stress Model for Eulerian multiphase. (6th April 2006) - Cokljat, D.; Slack, M.; Vasquez, S.A.; Bakker, A.; , G. Montante
This paper presents a way of modelling turbulence in multiphase flows within the context of the Reynolds-Stress Model. The model has been implemented in the general-purpose unstructured finite volume code Fluent V6. Two multiphase turbulence approaches were considered: mixture and dispersed models. The mixture model solves the Reynolds-stress transport equations on the mixture level only. The dispersed approach solves the Reynolds-stress transport equations for the continuous phase, while the turbulence closure for the dispersed phases is achieved by an extension of the theory of dispersion of discrete particles by homogeneous turbulence. The dispersed model was used to calculate bubbly flow over a cylindrical back-step and the flow in an unbaffled stirred vessel. The mixture approach was used to calculate an industrially relevant cyclone flow.